Analyzing Students' Learning Obstacles on Distance Material in Three Dimensional - Sukri Sukri; Sufyani Prabawanto; Dian Usdiyana (Postgraduate, University of Mataram, 2023)
This study was intended to identify learning obstacles faced by students on the distance between two points and the distance between point-to-line materials. The data in this study was obtained through a test, interview, and documentation of students who have learned the materials. The research method used was the qualitative method with a case study approach. This study involved 33 students of class XII and a teacher as a participant. Learning obstacles found in this study were ontogenical, didactical, and epistemological obstacles. The ontogenical obstacles were the students' lack of basic geometry ability and counting operations of the square root which caused the students to make mistakes in applying the Pythagoras formula, determining the position of perpendicular lines, as well as completing arithmetic operations of the square root. The didactical obstacle was the fact that students were only emphasized on using a quick formula to solve three-dimensional problems. This fact resulted in the uncompleted concept received by students. Consequently, the students forget the proper procedure for solving the problems easily, and they tend to make mistakes in applying the quick formula. The epistemological obstacle was the lack of students' comprehension of a concept to determine the distance between a point to a line if the triangle which is formed is not a right triangle. This lack of comprehension caused the students can’t solve a mathematics problem. The implication of this study is learning materials used by students should be arranged based on students' needs which consider the analysis of learning obstacles so that the learning objectives can be achieved